SISTEMA DE COMBATE A INCÊNDIO UTILIZANDO A TECNOLOGIA DE ÁGUA NEBULIZADA (WATER MIST) EM INSTALAÇÕES OFFSHORE - Costa Neto, Felicio Pedro da (2008)
Offshore rigs and petroleum production units usually require some fire protection and they have many compartments to protect. Water mist system is one among the fire fighting systems available. The water mist system is suitable for liquids fire (class B), solid fuels fire (class A) and electric equipments (class C). It uses small water droplets for fire extinction, suppression and fire control. Test protocols were developed by International Maritime Organization (I.M.O.) aside with National Fire Protection Association (NFPA). These institutions emitted in 2001 the standard NFPA 750 Standard on Water Mist Fire Protection. These protocols and the standard are references for design developments and tests and are used by companies worldwide. This paper proposes to spread the water mist technology, exploiting its operation mechanisms, its application on offshore rigs and petroleum production units, stressing the test of this technology on electric panels.